Diffusion changes predict cognitive and functional outcome: The LADIS study. Issue 5 (19th February 2013) - Jokinen, Hanna; Schmidt, Reinhold; Ropele, Stefan; Fazekas, Franz; Gouw, Alida A.; Barkhof, Frederik; Scheltens, Philip; Madureira, Sofia; Verdelho, Ana; Ferro, José M.; Wallin, Anders; Poggesi, Anna; et al.
<x xml:space="preserve">Abstract</x> Objective A study was undertaken to determine whether diffusion‐weighted imaging (DWI) abnormalities in normal‐appearing brain tissue (NABT) and in white matter hyperintensities (WMH) predict longitudinal cognitive decline and disability in older individuals independently of the concomitant magnetic resonance imaging (MRI) findings. Methods A total of 340 LADIS (Leukoaraiosis and Disability Study) participants, aged 65 to 84 years, underwent brain MRI including DWI at baseline. Neuropsychological and functional assessments were carried out at study entry and repeated annually over a 3‐year observational period. Linear mixed models and Cox regression survival analysis adjusted for demographics, WMH volume, lacunes, and brain atrophy were used to evaluate the independent effect of the DWI measures on change in cognitive performance and functional abilities. Results The mean global apparent diffusion coefficient (ADC) and the relative peak height and peak position of the ADC histogram in NABT predicted faster rate of decline in a composite score for speed and motor control. Higher mean ADC and lower peak height were also related to deterioration in executive functions and memory (specifically working memory), with peak height also being related to more rapid transition to disability and higher rate of mortality. Mean ADC in WMH had less pronounced effects on cognitive and functional outcomes. Interpretation DWI microstructural changes in NABT predict faster decline in psychomotor speed, executive functions, and working memory regardless of conventional MRI findings. Moreover, these changes are related to functional disability and higher mortality. Ann Neurol 2013;73:576–583